Chronic Obstructive Pulmonary Disease Treatment and Pharmacist-Led Medication Management - Li LC; Han YY; Zhang ZH; Zhou WC; Fang HM; Qu J; Kan LD (Dove Medical Press, 2021)
Liu-Cheng Li,1,* Yong-Yue Han,2,* Zhi-Hui Zhang,3,4 Wen-Cheng Zhou,5,6 Hong-Mei Fang,1 Jiao Qu,7 Lian-Di Kan1 1Department of Pharmacy, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou 310016, People’s Republic of China; 2School of Pharmacy, Dalian Medical University, Dalian 116044, People’s Republic of China; 3Shanghai TCM-Integrated Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai 200082, People’s Republic of China; 4Shanghai TCM-Integrated Institute of Vascular Anomalies, Shanghai 200082, People’s Republic of China; 5Department of Pharmacy, The First Affiliated Hospital of Zhejiang Chinese Medicine University, Hangzhou 310006, People’s Republic of China; 6Department of Pharmacy, Zhejiang Provincial Hospital of Traditional Chinese Medicine, Hangzhou 310006, People’s Republic of China; 7State Key Laboratory of Pharmaceutical Biotechnology, Department of Biotechnology and Pharmaceutical Sciences, School of Life Science, Nanjing University, Nanjing 210023, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lian-Di KanDepartment of Pharmacy, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou 310016, People’s Republic of ChinaTel +86-571-86006803Email 3198004@zju.edu.cnJiao QuState Key Laboratory of Pharmaceutical Biotechnology, Department of Biotechnology and Pharmaceutical Sciences, School of Life Science, Nanjing University, Nanjing 210023, People’s Republic of ChinaTel +86-25-89687620Email qujiao19920819@163.comAbstract: Chronic obstructive pulmonary disease (COPD) is the fourth leading cause of death across the globe. Its repeated exacerbation will seriously worsen the quality of life, aggravate the patients’ symptoms, and bring a heavy burden on the patients and the society. Understanding the current status of drug therapy and the role of pharmaceutical care is essential for the management of COPD. In addition to the drugs already on the market, recent clinical trials also show that emerging novel drugs for treating COPD are being developed to prevent the symptoms, reduce the frequency of acute exacerbation, and improve the quality of life. Recent progress in new drug research should lead to novel treatment options for COPD patients in future clinical practice. The pharmaceutical care has shown significantly favourable impacts on addressing drug-related problems, supporting its vital role in the management of COPD, especially when there are a wide range of therapeutic agents. This review not only provides an overview of current treatment strategies but also further underlines the importance of new drug development and pharmaceutical care for patients with COPD.Keywords: chronic obstructive pulmonary disease, drugs, clinical trial, complications, pharmaceutical care